Analisa Hubungan Antara Kompensasi, Promosi Jabatan Dengan Kinerja Karyawan - Dedy Syahyuni (LPPM Universitas Trunojoyo Madura, 2021)
Employee performance or employee work performance is one of the keys to improving and maximizing organizational functions, either government organizations or private organizations (companies). With good employee performance, companies or government organizations can work effectively and efficiently because all work can be done in the right way and the use of all resources (time, cost and so on) can be used optimally. Various efforts have been made to increase and improve the level of employee performance; some have tried to maximize the work motivation component and so on. This paper tries to connect the compensation variables, job promotion and its relation to employee performance. From the calculation results, it is found that there is a relationship of 0.487 or a moderate level relationship between the compensation variable and the answer promotion with employee performance. The place for data collection was carried out at BPJS Ketenagakerjaan, Depok Branch, where respondents totaled 40 employees with a significance level of 5%.